2010
DOI: 10.4236/jwarp.2010.26062
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Approach Based Management Model for Irrigation Planning

Abstract: The objective of this paper is to develop the irrigation planning model and to apply the same in the form of Multi Objective Fuzzy Linear Programming (MOFLP) approach for crop planning in command area of Jayakwadi Project Stage I, Maharashtra State, India. To formulate MOFLP model various Linear Programming (LP) models are developed to optimize the Net Benefits (NB), Crop/Yield Production (YP), Employment Generation (EG) and Manure Utilization (MU) for which the objective function and constraints are crisp in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 10 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…The detailed description of Case-I, given by Regulwar and Gurav (2010). From this solution, it is observed that the area to be irrigated is constant in case of Chilies (TS) and Sorghum (K) under LP model and MOFLP model solution.…”
Section: Results Analysismentioning
confidence: 98%
“…The detailed description of Case-I, given by Regulwar and Gurav (2010). From this solution, it is observed that the area to be irrigated is constant in case of Chilies (TS) and Sorghum (K) under LP model and MOFLP model solution.…”
Section: Results Analysismentioning
confidence: 98%
“…These objective functions are maximized separately subjected to constraints (Equations (5) to (17) Table 2 in the form of mathematical Equation (24) to (27 as (x * ) represented in Table 2. In addition, the results MOFLP model, and TPMOFLP model have been shown graphically in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…Regulwar and Anand Raj ( [25,26]) have developed a monthly Multi Objective Genetic Algorithm Fuzzy Optimization model. Regulwar and Gurav [27] have developed the MOFLP irrigation planning model, which considers the fuzziness in four objectives of the case study. Regulwar and Gurav [28] have presented the study on irrigation planning under uncertainty considering different cases using MOFLP approach.…”
Section: Introductionmentioning
confidence: 99%
“…These objectives were minimum completion time and crashing costs required to be optimized simultaneously. Regulwar and Gurav [31] developed a multi objective fuzzy linear programming approach for crop planning in command area of Jayakwadi project stage I, Maharashtra State, India. Four objectives were optimized (maximized) simultaneously.…”
Section: Literature Reviewmentioning
confidence: 99%